ANALISIS PENENTUAN JUMLAH TENAGA KERJA BERDASARKAN KAPASITAS PRODUKSI UMKM PIA â€œMAHEN - Nur Rizka Athirah; Handy Febri Satoto (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
Pia "Mahen", one of the MSMEs that produces pia cakes in an amount of around Â± 7000 pieces every day with a total of 3 outlets with a production location in the center. The current state of production capacity is still not 100% able to meet customer demand so that there are several requests that are rejected due to limited production capabilities. Pia Mahen has 1 labor group of 8 production workers and 1 baking worker with regular working hours of 7 hours and overtime of 3 hours. With the calculation of standard capacity, it can be known the standard capabilities of labor and oven facilities within regular and overtime working hours so that the required labor can also be calculated. With alternatives including the addition of production labor groups or the addition of odd hours, it can be considered and calculated the average percentage of the difference in income if all requests are met with the production costs incurred, namely 17.75% on the alternative of adding permanent labor and 21.44% on the addition of odd labor. In addition, there is a transportation method that can help optimize demand fulfillment with the amount of production every day so that overtime hours and days off are also obtained